Medical students with low self-efficacy bolstered by calling to medical speciality - Goodin, Joel B. (Bohn Stafleu van Loghum, 2014)
This study was performed to understand the degree to which medical students’ self-efficacy (SE) moderates the influence of calling on students’ speciality commitment, emphasizing the need to understand variables that predict primary care specialization. The researchers hypothesized that students who perceived their career as a calling would be more committed to their speciality, especially when students had high SE. Medical students (Years 1–4; N = 152) completed an online survey to rate their calling, speciality commitment, and SE. Calling was measured by the Brief Calling scale (Dik et al., J Career Assess 20:242–263, 2012), while speciality choice was measured by Hollenbeck et al. (J Appl Psychol 74:18–23, 1989) measure of commitment. SE was measured by the Jerusalem and Schwarzer's general SE scale (see Scholz et al., Eur J Psychol Assess 18:242–51, 2002). Calling (r = 0.24, p < 0.01) and SE (r = 0.20, p < 0.05) were found to moderately correlate with speciality commitment, thus emphasizing the possibility that they may have an interaction. The interaction of calling and SE significantly predicted speciality commitment (β = −0.20, t(148) = −2.55, p < 0.05) and explained a significant proportion of variance in speciality commitment (R (2) = 0.12, F(3, 148) = 6.875, p < 0.001). Students with a high presence of calling may have high speciality commitment, despite low SE.